Pengaruh Atribut Hotel dan Promosi Penjualan Terhadap Keputusan Menginap di Crowne Plaza Hotel Bandung - Wardani, Yudha; Agustiani, Indah Nur (Tourism Scientific Journal, 2023)
Crowne Plaza is one of the hotel brands from the world's leading hotel group, namely IHG (Intercontinental Hotel Group). However, during the hotel opening in the 2017-2018 period, Crowne Plaza's room occupancy rate was still inferior to similar competitors, even though Crowne Plaza is a five-star hotel that has a high occupancy rate in the city of Bandung for the five-star segment with an average occupancy of above 50%. . However, all these advantages do not make Crowne Plaza the top occupancy five star hotel in Bandung. The results of the research show that product attributes consisting of security, quality & dependability, reputation, physical appearance, location and price have a significant influence on the decision to stay overnight. The results of research on sales promotions consisting of Corporate Rate price, Credit Card Discounts and Bundle Event promos have a significant influence on consumer purchasing decisions. Likewise, from the results of research that the author has researched, it is known that product attributes and sales promotions have a significant influence on the decision to stay at the Crowne Plaza Hotel Bandung. Based on the results of calculations carried out by the author, the influence of product attributes and sales promotions on the decision to stay at the Crowne Plaza Hotel Bandung is in the strong category. Product attributes (X1) and sales promotions (X2) together influence the decision to stay (Y) by 59.6% and the remaining 16.34% taken from the epsilon number in Figure 1 of the path diagram is influenced by other factors that were not included in the research.